Immunosuppression Induced by a Conditioned Stimulus Associated With Cocaine Self-Administration - Marta Kubera; Malgorzata Filip; Boguslawa Budziszewska; Agnieszka Basta-Kaim; Karolina Wydra; Monika Leskiewicz; Magdalena Regulska; Lucylla Jaworska-Feil; Edmund Przegalinski; Anna Machowska; Wladyslaw Lason (Elsevier, 2008)
Cocaine addiction is known to impair immune system function, but the effects of repeated treatment with cocaine in a self-administration model, its withdrawal as well as reinstatement of cocaine-seeking behavior on cell-mediated immunity are not well known. Cocaine self-administered for 18 days induced a significant increase in spleen weight, plasma corticosterone levels, interleukin (IL)-10, and tumor necrosis factor-α production, while concanavalin A-stimulated proliferation responses of peripheral blood T-lymphocytes and interferon-γ production by splenic lymphocytes were not altered. After 10 days withdrawal from cocaine, reinstatement of cocaine seeking behavior induced either by a priming dose of the drug (unconditioned stimulus), by cue previously associated with cocaine self-administration (conditioned stimuli), or by both these stimuli evoked similar changes in several immunological parameters, for example, a decrease in relative spleen weight, proliferative activity of splenocytes, and their ability to produce IL-10. The results showed that the cue previously associated with cocaine suppressed some parameters of cell-mediated immunity to the same degree as reexposure to cocaine. The present study provides the first evidence that alterations of immune status can be conditioned by environmental stimuli paired with cocaine administration. Keywords:: cocaine, extinction, relapse, self-administration, immune system